Review of Alexander Rehding. 2003. Hugo Riemann and the Birth of Modern Musical Thought. New York and Cambridge: Cambridge University Press - Kim, Youn (Current Musicology, 2003)
For a long time, historical studies of the sciences adopted a perspective variously known by the names presentist, teleological, essentialist, or Whiggish. Although these expressions carry slightly different meanings, we may roughly characterize this approach as an attempt to read the past in terms of present concerns; past scientific theories that had proven to be “wrong” and displaced by “right” theories are regarded as inferior fringe elements in the history of modern sciences. This approach is, of course, now passe. Most historical studies of the sciences, especially since the publication of Thomas Kuhn’s influential work, are not afraid to explore neglected scientific concepts and theories, and tend to rely heavily on the conceptual and cultural frameworks derived from areas other than science itself. I find it appropriate, therefore, to begin the review of Alexander Rehding’s Hugo Riemann and the Birth of Modern Musical Thought with a discussion of the historiography of science. First, the union of history and science-as well as that of history and music theory-presents some problems. Although it may be naIve, it is undeniable that most people still feel odd about the joining of science and history: the former is forward-looking and concerned with nature, whereas the latter is retrospective and deals with humanity. Likewise, the conjunction of music theory and history raises some conceptual difficulties. In Thomas Christensen’s words, music theory is a “subject that notoriously resists its own history” (2002: 1). Second, the parallelism between science and music theory is significant in studies of late nineteenth-century music theory, particularly in the study of Hugo Riemann’s ideas. Given that many of these theories aspired to scientific grounding, we may parallel historical approaches to the music theory of this period with historiographies of science. In attempting to discuss the shift in perspective in the realm of music theory’s history, we find Riemann’s notion of “harmonic dualism” the best case in point. Riemann believed that “minor triads are symmetrically opposed to major triads and work upsidedown” (Rehding 2003:7), an idea that was quickly discredited by many later generation theorists.